Sex differences in incidence rate, and temporal changes in surgical management and adverse events after hip fracture surgery in Denmark 1997–2017: a register-based study of 153,058 hip fracture patients - Wahlsten, Liv R; Palm, Henrik; Gislason, Gunnar H; Brorson, Stig (Acta Orthopaedica, 2021)
Background and purpose — Extensive research and national multidisciplinary programs have striven to introduce uniform standards of treatment and mitigate mortality and adverse events after hip fracture surgery over the past decades. A large-scale overview of temporal developments in hip fracture surgery and care is warranted. Patients and methods — We studied Danish patients aged ≥ 60 years, sustaining their first ever hip fracture between 1997 and 2017. Patients were identified from the Danish National Patient Registry (DNPR). Incidence rates of first hip fracture were calculated per 1,000 patient-years and stratified by age group and sex. Information on preinjury living settings, comorbidities, and medications were obtained from national administrative registers. Type of fracture and treatment choice were recorded, and patients were followed for 1 year to observe mortality, readmission, and surgical complications. Results — Data from 153,058 patients was analyzed. Incidence rate decreased in both sexes, but only led to a reduction in the annual number of hip fractures in the female population. Choice of surgery shifted away from sliding hip screws and parallel implants (SHS-PI), towards intramedullary nailing and hemi-/arthroplasties for trochanteric and femoral neck fractures, respectively. Pre-injury diagnosed morbidity and 1-year readmissions increased contrary to mortality. Median age remained stable around 83 (IQR 77–88) for women and 80 (IQR 73–86) for men. Interpretation — Over the past 2 decades important aspects of hip fracture management have improved. However, sex differences were observed, and men remain more vulnerable than women in terms of morbidity, mortality, and incidence rate.